Maintenance tocolysis with nifedipine in threatened preterm labour: 2‐year follow up of the offspring in the APOSTEL II trial. (27th August 2015) - van Vliet, EOG; Seinen, L; Roos, C; Schuit, E; Scheepers, HCJ; Bloemenkamp, KWM; Duvekot, JJ; van Eyck, J; Kok, JH; Lotgering, FK; van Baar, A; van Wassenaer‐Leemhuis, AG; et al.
Abstract : Objective: To evaluate long‐term effects of maintenance tocolysis with nifedipine on neurodevelopmental outcome of the infant. Design, Setting and Population: Follow up of infants of women who participated in a multicentre randomised controlled trial on maintenance tocolysis with nifedipine versus placebo. Methods: Two years after the APOSTEL II trial on maintenance tocolysis with nifedipine versus placebo, we asked participants to complete the Ages and Stages Questionnaire. Main outcome measures: Infant development was measured in five domains. Developmental delay was defined as a score of ≤1 SD in one or more developmental domains. We performed exploratory subgroup analysis in women with preterm prolonged rupture of the membranes, and in women with a cervical length <10 mm at study entry. Results: Of the 276 women eligible for follow up, 135 (52.5%) returned the questionnaire, encompassing data of 170 infants. At 2 years of age, infants of women with nifedipine maintenance tocolysis compared with placebo had a higher overall incidence of fine motor problems (22.2 versus 7.6%, OR 3.43, 95% CI 1.29–9.14, P  = 0.01), and a lower incidence of poor problem‐solving (21.1 versus 29.1%, OR 0.27, 95% CI 0.08‐0.95, P  = 0.04). Conclusions: This follow‐up study revealed no clear benefit of nifedipine maintenance tocolysis at 2 years of age. As short‐term adverse perinatal outcome was not reduced in the original APOSTEL II trial, we conclude that maintenance tocolysis does not appear to be beneficial at this time. Tweetable abstract: No clear benefit of nifedipine maintenance tocolysis in preterm labour on 2‐year infant outcome. Tweetable abstract: No clear benefit of nifedipine maintenance tocolysis in preterm labour on 2‐year infant outcome.